2013
DOI: 10.4049/jimmunol.1202916
|View full text |Cite
|
Sign up to set email alerts
|

IL-27 Receptor Signaling Regulates CD4+ T Cell Chemotactic Responses during Infection

Abstract: IL-27 exerts pleiotropic suppressive effects on naïve and effector T cell populations during infection and inflammation. Surprisingly, however, the role of IL-27 in restricting or shaping effector CD4+ T cell chemotactic responses, as a mechanism to reduce T cell-dependent tissue inflammation, is unknown. In this study, using Plasmodium berghei NK65 as a model of a systemic, pro-inflammatory infection, we demonstrate that IL-27R signalling represses chemotaxis of infection-derived splenic CD4+ T cells in respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 42 publications
(51 reference statements)
1
18
0
Order By: Relevance
“…Anti-inflammatory responses following ingestion of some polyphenol-containing supplements may be, in part, a result of enhanced type I IFN responses through enhanced expression of anti-inflammatory cytokines IL-10 and IL-27. IL-27R signaling, in particular, has been shown recently to decrease specifically inflammatory cytokine expression, primarily IFN-␥, and trafficking by CD4 ϩ T cells [25,26]. These cells are a primary source of inflammation in the mouse model of colitis [27].…”
Section: Resultsmentioning
confidence: 99%
“…Anti-inflammatory responses following ingestion of some polyphenol-containing supplements may be, in part, a result of enhanced type I IFN responses through enhanced expression of anti-inflammatory cytokines IL-10 and IL-27. IL-27R signaling, in particular, has been shown recently to decrease specifically inflammatory cytokine expression, primarily IFN-␥, and trafficking by CD4 ϩ T cells [25,26]. These cells are a primary source of inflammation in the mouse model of colitis [27].…”
Section: Resultsmentioning
confidence: 99%
“…Control of inflammation during parasitic infection is achieved mostly by Treg cells, IL-10 producing CD4+ T cells, and IL-27R signaling [126128]. Recently, Couper and colleagues have demonstrated that IL-27 is responsible for inhibiting the CCL4 and CCL5 responding CD4+ T cells that migrate to Plasmodium infection in the liver and does so by directly downregulating CCR5 expression [129]. Surprisingly, considering the significant volume of studies investigating many of these immunomodulatory pathways, there is little understanding of chemokine recruitment of regulatory cell populations during parasitic infection [95].…”
Section: Parasite Dissemination and Cell Recruitment To Other Organsmentioning
confidence: 99%
“…The mechanisms underlying the ability of IL-27 to regulate Th1 inflammatory T cells during Plasmodium infection are just now becoming clear. In contrast to its ability to induce specific populations of Tregs in the Toxoplasma -infected gut, IL-27 signaling in effector T cells during blood stage Plasmodium infection appears to suppress inflammatory Th1 cell responsiveness to specific chemokines and cytokines [48,49]. A recent report showed that IL-27 signaling in highly polarized Th1 cells led to marked reductions in the expression of the CCR5 chemokine receptor.…”
Section: Immunoregulation By Secreted Factorsmentioning
confidence: 99%
“…A recent report showed that IL-27 signaling in highly polarized Th1 cells led to marked reductions in the expression of the CCR5 chemokine receptor. The authors contend that dysregulation of CCR5-dependent T cell chemotaxis contributes to the ability of IL-27 to suppress inflammatory Th1 T cell migration to the spleen during Plasmodium infections [49]. Moreover, a subsequent study examining pathogenic Th1 cells induced by P. berghei infection found that IL-27 limited T cell responsiveness to IL-12 [48], which is a critical positive regulator of Th1 cell differentiation and survival as discussed above.…”
Section: Immunoregulation By Secreted Factorsmentioning
confidence: 99%